Treatment outcome of children with persistent Diarrhoea admitted to an Urban Hospital, Dhaka during 2012-2013 - Mustafa Mahfuz; Mohammed Ashraful Alam; Shoeb Bin Islam; Nurun Nahar Naila; Mohammod Jobayer Chisti; Nur Haque Alam; Shafiqul Alam Sarker; Tahmeed Ahmed (BMC, 2017)
Abstract Background Despite availability of treatment guidelines, persistent diarrhoea (PD) has been a major contributor of diarrhoeal deaths in low and middle income countries. We evaluated the outcome of children under the age of 5 years who were treated for PD using management algorithm with locally available foods in a diarrhoeal disease hospital in Dhaka. Methods We extracted retrospective data from electronic database for all the under-five children admitted for PD in the Longer Stay Ward and Intensive Care Unit of the Dhaka hospital at icddr,b between 2012 and 2013. Descriptive analysis was done to explore available baseline socio-demographic, nutritional, and co-morbid statuses, pathogens from stool isolates, duration of treatment, use of antibiotics, duration of hospital stay and treatment success rates. We sought to investigate above mentioned descriptive features in addition to associated factors with time to recover from PD using survival analysis with Cox proportional hazard model. Results A total number of 426 children with a median age of 7.46 (inter-quartile range IQR; 5.39, 9.43) months were admitted for PD during the study period. Of these, 95% of children were recovered from PD and discharged from the hospital. The median duration of treatment response was 6 (IQR 4, 9) days. The case fatality rate was 1.17%. Multivariate analysis among the children of 6 months or less showed that the rate of recovery from PD was 57% lower in children with severe stunting compared to those without severe stunting (HR 0.43, 95% CI 0.22, 0.88, p < 0.05), 42% lower in children with severe wasting (HR 0.58, 95% CI 0.36, 0.95, p < 0.05), and 81% reduced in children who developed hospital acquired infection (HAI) compared to those without HAI (HR 0.19, 95% CI 0.06, 0.62, p < 0.05). Among the children who were more than 6 months old, age in months (HR 1.05, 95% CI 1.02, 1.09) and female gender (HR 1.41, 95% CI 1.09, 1.84) had better rates of recovery from PD (p < 0.05). Moreover, among children more than 6 months of age, HAI (HR 0.44, 95% CI 0.26, 0.75), and antibiotic use (HR 0.40, 95% CI 0.28, 0.56) were associated with impeded recovery rates from PD (p < 0.05). Conclusion The treatment guideline for persistent diarrhoea patients followed at icddr,b Dhaka hospital was found to be successful and can be used in other treatment facilities of Bangladesh and other developing countries where any treatment algorithm for PD is unavailable. More emphasis is required to be given for the prevention of hospital acquired infection that may help to limit the use of antibiotic in order to enhance the recovery rate from PD.